Pelatihan Pembuatan Konten Promosi Bagi Pelaku UMKM Dengan Menggunakan Aplikasi CANVA - Faldy Irwiensyah; Arafat Febriandirza (CV. Multi Kreasi Media, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are currently facing increasingly intense competition, particularly in the fields of digital marketing and branding. These two aspects have become essential skills that MSMEs must possess to compete in the digital space. The rapid development of digital competencies requires MSMEs to be ready to adapt by optimizing their use of digital media. Effective and targeted use of digital media is one of the key factors for MSMEs to achieve success. Therefore, MSME entrepreneurs need to enhance their ability to create engaging and interactive marketing content for promotion on digital platforms. As part of a community service initiative, training and mentoring activities were conducted to support MSME entrepreneurs, specifically DINARNIA Muslim Clothing Store. This training aimed to teach strategies for creating promotional content on digital media using the Canva application. Through this program, MSME entrepreneurs learned to utilize Canva, starting from creating an account, logging into the application, selecting templates, and adding images and text to the chosen templates. It is hoped that this training will assist MSMEs in promoting their products or services digitally, increasing sales, and ensuring business sustainability. The participants gained valuable insights into effectively using Canva, enabling them to advance their MSMEs to a better level.